Concurrent Primary Follicular Lymphoma and a Mature Cystic Teratoma of the Ovary: A Case Report and Review of Literature - Sakara Hutspardol; Yi Li; Valerie Dube; Jan Delabie (Case Reports in Pathology)
Primary lymphoma concurrent with teratoma of the ovary is exceedingly rare. Based on our review of the literature, there are only 8 case reports describing concurrent primary diffuse large B-cell lymphoma and teratoma. Here, we report the first case of primary follicular lymphoma concurrent with mature ovarian cystic teratoma, which, to our knowledge, has not been described in the literature.